URZĄD CENZORA W ŚWIETLE ‘NOCY ATTYCKICH’ AULUSA GELLIUSA - Tarwacka, Anna (Zeszyty Prawnicze, 2016)
THE OFFICE OF CENSOR IN THE LIGHT OF THE NOCTES ATTICAE BY AULUS GELLIUS Summary The aim of the article is to analyse the passages in Aulus Gellius’ Noctes Atticae on the office of censor. This magistracy seems to have interested Gellius for various reasons: linguistic matters concerning the meaning of archaic words, but also things inspired by the books Gellius had read and where he found some amusing anecdotes which he decided to record. He treated the censors’ office as one of the most important Roman magistracies, and described the censors’ power to conduct auspices, issue edicts, deliver speeches, control morals, conduct the census, make the list of senators and equites, and mete out punishment with the issue of the censorial note. However, he never mentioned the censors’ administrative powers such as the conclusion of public contracts and the supervision of public places. The Attic Nights are not arranged in a systematic order, but they are a priceless source of information on legal institutions such as the office of censor; Gellius has saved for us some direct quotations from otherwise lost works by Roman orators and jurists.